Kedudukan Putusan Mahkamah Konstitusi Dalam Pembentukan Undang-Undang di Indonesia - Liana Nasir; Syamsul Rijal; Aksan Akbar, Muhamad (JURNAL USM LAW REVIEW, 2025)
This study aims to analyze the position of the Constitutional Court's decision in the formation of laws and to examine the legal implications if the laws formed are in conflict with the Constitutional Court's decision. This study is important to conduct considering the polemic of alleged non-compliance of state administrators with the Constitutional Court's decision, especially in the formation of laws. This study is different from several previous studies because it examines the position of the Constitutional Court's decision and the legal implications of laws formed in conflict with the Constitutional Court's decision. Using a normative legal research method. The results obtained from this study are that the Constitutional Court's decision is a source of law in the formation of laws as stipulated in Article 10 paragraph (1) letter d of Law No. 12 of 2011, that one of the materials that must be included in the law is the follow-up to the Constitutional Court's decision. The legal implications of the formation of laws that are in conflict with the Constitutional Court's decision are that it will cause legal uncertainty, can harm human rights, and the law can be submitted for judicial review to the Constitutional Court. The Constitutional Court's decision is the official interpretation of the 1945 Constitution. Therefore, the DPR and the President are obliged to follow up on it in the formation of laws, so that the resulting laws can provide justice, benefits, and legal certainty as well as protection of human rights.   Penelitian ini bertujuan untuk menganalisis kedudukan putusan Mahkamah Konstitusi dalam pembentukan undang-undang serta mengkaji implikasi hukum apabila undang-undang yang dibentuk bertentangan dengan putusan Mahkamah Konstitusi. Penelitian ini penting dilakukan mengingat adanya polemik dugaan ketidakpatuhan penyelenggara negara terhadap putusan Mahkamah Konstitusi khususnya dalam pembentukan undang-undang. Penelitian ini memiliki perbedaan dengan beberapa penelitian sebelumnya karena mengakaji kedudukan putusan Mahkamah Konstitusi dan implikasi hukum undang-undang yang dibentuk bertentangan dengan putusan Mahkamah Konstitusi.  Menggunakan metode penelitian hukum normatif. Hasil yang diperoleh dari penelitian ini yaitu putusan Mahkamah Konstitusi berkedudukan sebagai sumber hukum dalam pembentukan undang-undang sebagaimana ditentukan pada Pasal 10 ayat (1) huruf d UU No. 12 Tahun 2011, bahwa salah satu materi yang wajib dimuat dalam undang-undang adalah tindak lanjut atas putusan Mahkamah Konstitusi. Implikasi hukum pembentukan undang-undang yang bertentangan dengan putusan Mahkamah Konstitusi yakni akan menimbulkan ketidakpastian hukum; dapat merugikan hak asasi manusia; dan undang-undang tersebut dapat diajukan judicial review di Mahkamah Konstitusi. Putusan Mahkamah Kontitusi merupakan penafsiran resmi UUD 1945. Oleh karena itu, DPR dan Presiden wajib menindaklanjutinya dalam pembentukan undang-undang, agar undang-undang yang dihasilkan dapat memberikan keadilan, kemanfaatan dan kepastian hukum serta perlindungan terhadap hak asasi manusia.